2017
DOI: 10.1039/c7cy01571b
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum oxycarbonate modified Cu/Al2O3 catalysts for selective hydrogenolysis of glucose to propylene glycol: base site requirements

Abstract: Moderate and strong base sites play a key role in glucose hydrogenolysis over bifunctional Cu–La2O2CO3/Al2O3 catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…The total selectivity (63.5%) of 1,2-PDO and glycerol for glucose hydrogenolysis could be attributed to the basicity of Co 2 -Ca 4 -Al 3 . It has been reported that the basic sites could facilitate the isomerization of glucose to fructose and the C 3 -C 4 bond cleavage of fructose to produce GLA and DHA via retro-aldol condensation, which can be subsequently dehydrated and hydrogenated to 1.2-PDO . Notably, the byproducts EG, MeOH, and LA could also be degraded from GLA as discussed above.…”
Section: Resultsmentioning
confidence: 96%
“…The total selectivity (63.5%) of 1,2-PDO and glycerol for glucose hydrogenolysis could be attributed to the basicity of Co 2 -Ca 4 -Al 3 . It has been reported that the basic sites could facilitate the isomerization of glucose to fructose and the C 3 -C 4 bond cleavage of fructose to produce GLA and DHA via retro-aldol condensation, which can be subsequently dehydrated and hydrogenated to 1.2-PDO . Notably, the byproducts EG, MeOH, and LA could also be degraded from GLA as discussed above.…”
Section: Resultsmentioning
confidence: 96%
“…12 Additionally, the catalytic conversion of renewable and abundant carbohydrates, such as triose monosaccharides obtained from retro-aldol condensation of fructose, holds promise as an alternative route for 1,2-PDO production. 10,11,[13][14][15][16][17][18][19][20][21][22] Currently, cellulose, glucose, and fructose are the commonly used carbohydrate substrates (Table 1). 10,11,[13][14][15][16][17][18][19][20][21][22] Several catalysts have been employed for the conversion of cellulose to 1,2-PDO, including 5%Co/CeO x , 13 Fe 3 O 4 @SiO 2 /10% Ru-20% WO x , 14 5% Ru-Fe 3 O 4 / SiO 2 , 15 and CuCr(4) + Ca(OH) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…10,11,[13][14][15][16][17][18][19][20][21][22] Currently, cellulose, glucose, and fructose are the commonly used carbohydrate substrates (Table 1). 10,11,[13][14][15][16][17][18][19][20][21][22] Several catalysts have been employed for the conversion of cellulose to 1,2-PDO, including 5%Co/CeO x , 13 Fe 3 O 4 @SiO 2 /10% Ru-20% WO x , 14 5% Ru-Fe 3 O 4 / SiO 2 , 15 and CuCr(4) + Ca(OH) 2 . 11 Among these, a hybrid catalyst of copper chromium CuCr(4) with 2000 ppm Ca(OH) 2 exhibited the highest 1,2-PDO yield of 42.6% for a cellulose substrate under the conditions of 6.0 MPa H 2 , 245 °C, and 5 h. 11 This result emphasizes the signicant role of base sites (Ca(OH) 2 ) in catalyzing the isomerization of cellulose-unit glucose to fructose.…”
Section: Introductionmentioning
confidence: 99%
“…12 A series of metal combinations has been used for the production of C 2 /C 3 glycols from cellulose and glucose, over the last few years. Fe 3 O 4 @SiO 2 /Ru-WO x (32.7%), 11 Ni/AC + SnO (32.4%), 13 Ru/C + WO 3 /Al 2 O 3 + C ac (40.9%), 14 CuCr + Ca(OH) 2 (42.6% and 52.8%), 15,16 Ni/ZnO (34.4%), 17 Pd-WO x (5%)/Al 2 O 3 (60.8%), 18 Ni-W/b+ZnO (35.8%), 19 Ni/AC + La(OH) 3 (27.8%), 20 RuSn/AC (25%), 21 Ni/ZnO-CNT (15%), 22 Cu-WO x (0.8)/Al 2 O 3 (55%), 23 Pt/SiO 2 @Mg(OH) 2 (53.8%), 24 Cu/ La 2 O 2 CO 3 (32%), 25 Ni/NaY (69%), 26 Cu-Ce/g-Al 2 O 3 (62.7%), 27 and Ni-W 2 C/AC (38.5%) 28 are some of the few notable works on 1,2-PDO production from the various carbohydrate sources.…”
Section: Introductionmentioning
confidence: 99%